Measuring IGF-1 and IGFBP-3 profiles in women seeking assisted reproduction; relationship to ovarian reserve parameters, namely AFC and AMH (study 2). - John, John L Yovich; Syeda Zaidi; Minh DK Nguyen; Peter M Hinchliffe (GSC Biological and Pharmaceutical Sciences, 2020)
This is the second of five studies undertaken on women preparing for assisted reproduction, to sequentially examine the relevance of the insulin-like growth factor (IGF) profile (IGF-1, IGFBP-3 and the IGFBP-3/ IGF-1 ratio) which, in children, provides the essential criteria to identify the GH-deficient individual. Whilst our first, published study, focussed on clinical parameters, this study examines its relevance to the two parameters which define the ovarian reserve. The first, that of the antral follicle count (AFC), shows highly significant, sequential changes across 4 age groups ranging from high counts in the younger women <35 years and low counts in the older women, namely those aged 35-39 years, those aged 40-44 years and those aged ≥45 years (p<0.0001). Similarly, the serum levels of anti-Mullerian hormone (AMH), a later introduced marker of ovarian reserve, also showed highly significant sequential changes across the 4 age groups with high levels recorded in the young women and low counts in the older women (p<0.0001). At the higher AFC range, concordance between AFC groups and AMH groups was high at r=0.79 for precise matching and r=0.95 when neighbouring groups were included. The correlation was also clear with inter-quartile AMH levels ranging 27 pmol/L to 50 pmol/L across the higher AFC groups and 8 pmol/L to 10 pmol/L in the lowest groupings. However, IGF profiles showed no significant variations across the entire range, neither for the AFC nor for the AMH groups. Our next study will report on the relevance of the IGF profile to clinical outcomes.